Challenges and Opportunities for the Position and Function of Indonesian in the Future - Lubis, Fitriani; Purba, Fernando Marulitua; Hafizh, Fakhri; Limbong, Falentina; Panjaitan, Fransiska Veronita; Pakpahan, Rosinta; Gea, Samuel; Chandra, Syakira Pasha (Lembaga Riset Mutiara Akbar, 2023)
The Indonesian language faces both challenges and opportunities in the future. On the one hand, the increasing globalization and the dominance of English as a global language pose a threat to the position and function of Indonesian. The main challenge to the position and function of Indonesian is the increasing dominance of English. English is the lingua franca of the world, and it is used in many international contexts. This can make it difficult for Indonesians to compete with native English speakers in the global market. Additionally, the use of English in Indonesia is increasing, especially among the younger generation. This can lead to a decline in the use of Indonesian, and a loss of the language's unique identity. The growing national consciousness in Indonesia is leading to a renewed appreciation for the language. This is reflected in the increasing use of Indonesian in government, education, and media. The future of the Indonesian language is uncertain. However, the language has the potential to thrive if Indonesians can embrace the challenges and seize the opportunities that lie ahead.